Sustainable Green Processing of Grape Pomace Using Micellar Extraction for the Production of Value-Added Hygiene Cosmetics - Tomasz Wasilewski; Zofia Hordyjewicz-Baran; Magdalena Zarębska; Natalia Stanek; Ewa Zajszły-Turko; Magdalena Tomaka; Tomasz Bujak; Zofia Nizioł-Łukaszewska (Molecules, 2022)
This study sought to evaluate the possibility of using grape pomace, a waste material from wine production, for the preparation of cosmetic components. Following the existing clear research trend related to improving the safety of cleansing cosmetics, an attempt was made to determine the possibility of preparing model shower gels based on grape pomace extract. A new method for producing cosmetic components named loan chemical extraction (LCE) was developed and is described for the first time in this paper. In the LCE method, an extraction medium consisting only of the components from the final product was used. Thus, there were no additional substances in the cosmetics developed, and the formulation was significantly enriched with compounds isolated from grape pomace. Samples of the model shower gels produced were evaluated in terms of their basic parameters related to functionality (e.g., foaming properties, rheological characteristics, color) and their effect on the skin. The results obtained showed that the extracts based on waste grape pomace contained a number of valuable cosmetic compounds (e.g., organic acids, phenolic compounds, amino acids and sugars), and the model products basis on them provided colorful and safe natural cosmetics.